A new oil/membrane approach for integrated sweat sampling and sensing: sample volumes reduced from μL's to nL's and reduction of analyte contamination from skin. Issue 22 (18th October 2016) - Peng, R.; Sonner, Z.; Hauke, A.; Wilder, E.; Kasting, J.; Gaillard, T.; Swaille, D.; Sherman, F.; Mao, X.; Hagen, J.; Murdock, R.; Heikenfeld, J.
Abstract : Reported here is a new paradigm in sweat sampling and sensing, where sample volumes are dramatically reduced and where analyte contamination from the skin surface is mitigated. Abstract : Wearable sweat biosensensing technology has dominantly relied on techniques which place planar-sensors or fluid-capture materials directly onto the skin surface. This 'on-skin' approach can result in sample volumes in the μL regime, due to the roughness of skin and/or due to the presence of hair. Not only does this increase the required sampling time to 10's of minutes or more, but it also increases the time that sweat spends on skin and therefore increases the amount of analyte contamination coming from the skin surface. Reported here is a first demonstration of a new paradigm in sweat sampling and sensing, where sample volumes are reduced from the μL's to nL's regime, and where analyte contamination from skin is reduced or even eliminated. A micro-porous membrane is constructed such that it is porous to sweat only. To complete a working device, first placed onto skin is a cosmetic-grade oil, secondly this membrane, and thirdly the sensors. As a result, spreading of sweat is isolated to only regions above the sweat glands before it reaches the sensors. Best case sampling intervals are on the order of several minutes, and the majority of hydrophilic (low oil solubility) contaminants from the skin surface are blocked. In vitro validation of this new approach is performed with an improved artificial skin including human hair. In vivo tests show strikingly consistent results, and reveal that the oil/membrane is robust enough to even allow horizontal sliding of a sensor.